Diagnose- und Behandlungsstandards der zerebralen Sinus‑/Venenthrombose: Ergebnisse einer Onlineumfrage an deutschen Stroke-Units - Geisbüsch, Christina; Ringleb, Peter A.; Nagel, Simon (Der Nervenarzt, 2017)
Background and purposeThe aim of this survey was to characterize the current diagnostic and therapeutic strategies for thrombosis of the cerebral sinus and veins (CVT) performed in German stroke units (SU).MethodsBetween September 2015 and January 2016 all clinical heads of certified SUs in Germany were invited to participate in a standardized online survey. The survey concentrated on the basic characteristics of SUs, diagnostic and therapeutic procedures and was made anonymous if so desired. Frequencies were expressed as percentages and differences between regional stroke units (RSU) and supraregional (i. e. comprehensive) SUs (SRSU) were compared with the χ2-test or Fisher’s testResultsA total of 107 SU heads participated (response rate 42.8%) and 55.1% of these were RSUs. In 77.2% the diagnosis is made by magnetic resonance imaging angiography (MR-A, RSU 81.1% vs. SRSU 72.3%; p = 0.29). Of the SUs 79.1% determined d‑dimer if CVT is suspected (79.3% vs. 78.7%; p = 0.94) and 88.5% carried out screening for thrombophilia (89.5% vs. 87.2%; p = 0.72). Intravenous unfractionated heparin (67.2% vs. 70.2%; p = 0.74) or subcutaneous low molecular weight heparin (32.8% vs. 29.8%; p = 0.74) are first line therapy in all SUs. Invasive procedures, such as hypothermia (3.7% vs. 10.6%; p = 0.25), hemicraniectomy (26% vs. 63.9%; p = 0.0001), endovascular techniques (11.1% vs. 40.4%; p = 0.0007) and systemic thrombolysis (5.5% vs. 10.6%; p = 0.47) are performed more frequently in SRSUs. Of the SUs 18.5% already use new oral anticoagulants (10.7% vs. 27.7%; p = 0.027). Most of the SUs organize a follow-up visit (70.9% vs. 76.6%; p = 0.52) with a MRI (94.2% vs. 91.1%; p = 0.7) within the first 6 months.ConclusionThe survey revealed substantial homogeneity between RSUs and SRSUs and standards are mostly in line with the guidelines. Non-established procedures, such as invasive therapeutic procedures and the administration of new oral anticoagulants were used significantly more often in SRSUs.